Pengaruh Working Capital Turnover, Sales Growth, dan Liquidity Terhadap Profitability - Silalahi, Samuel Parlindungan; Malau, Harman; Hutabarat, Francis (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This research aims to examine whether there is an influence of working capital turnover, sales growth, and liquidity on profitability in companies within the advertising, printing, and media sub-sectors listed on the Indonesia Stock Exchange from 2019-2022. A descriptive method is used in this study to identify whether there is a relationship between variables, providing a detailed picture through linear regression analysis. Passive participation observation method is employed in data collection for this research. This approach involves studying, classifying, and analyzing secondary data such as audited financial reports and related information within the scope of this study. The dependent variable, profitability, is calculated using the ROA ratio. For independent variables, working capital turnover calculated by dividing earnings after tax by current assets minus current liabilities, sales growth is calculated by subtracting this year's total sales from last year's total sales and dividing by this year's total sales, and liquidity is calculated by dividing current assets by current liabilities. The results of this study indicate that simultaneously, working capital turnover, sales growth, and liquidity do not have an influence on profitability. Partially, working capital turnover and sales growth do not have an influence on profitability, but a positive relationship with profitability.